2021
DOI: 10.3390/ijms22115861
|View full text |Cite
|
Sign up to set email alerts
|

Diminazene Aceturate Stabilizes Atherosclerotic Plaque and Attenuates Hepatic Steatosis in apoE-Knockout Mice by Influencing Macrophages Polarization and Taurine Biosynthesis

Abstract: Atherosclerosis and nonalcoholic fatty liver disease are leading causes of morbidity and mortality in the Western countries. The renin–angiotensin system (RAS) with its two main opposing effectors, i.e., angiotensin II (Ang II) and Ang-(1–7), is widely recognized as a major regulator of cardiovascular function and body metabolic processes. Angiotensin-converting enzyme 2 (ACE2) by breaking-down Ang II forms Ang-(1–7) and thus favors Ang-(1–7) actions. Therefore, the aim of our study was to comprehensively eval… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 54 publications
0
9
0
Order By: Relevance
“…As we had determined that DIZE aggravated the infiltration of total macrophages after UUO ( Fig. 5 ), and because it was recently suggested that DIZE shifts macrophage polarization toward the profibrotic M2 phenotype in atherosclerotic lesions [ 26 ], we evaluated M2 macrophage accumulation by IHC staining. In addition, we measured levels of cytokines and chemokines involved in M2 macrophage survival and polarization.…”
Section: Resultsmentioning
confidence: 99%
“…As we had determined that DIZE aggravated the infiltration of total macrophages after UUO ( Fig. 5 ), and because it was recently suggested that DIZE shifts macrophage polarization toward the profibrotic M2 phenotype in atherosclerotic lesions [ 26 ], we evaluated M2 macrophage accumulation by IHC staining. In addition, we measured levels of cytokines and chemokines involved in M2 macrophage survival and polarization.…”
Section: Resultsmentioning
confidence: 99%
“…The modulation of LPS activity via arylamidines and the potential implications regarding potential treatments of numerous diseases associated with aberrant immune activation and coagulation have led to a flurry of animal model studies, including (i) amelioration of neurological pathologies (Alzheimer’s) [ 55 ]; (ii) cardiac (atherosclerotic plaque stabilization, cardiac fibrosis) [ 56 , 57 , 58 ]; (iii) pulmonary (hypertension) [ 59 ]; (iv) liver (injury and biliary fibrosis) [ 60 ]; (v) diabetic (type 1) [ 61 ]; (vi) acute radiation exposure/damaged tissue (ARE) [ 62 ] ( Table 2 ).…”
Section: Bats Pangolins Parasites and Diarylamidines: Making The Conn...mentioning
confidence: 99%
“…Additionally, Mas-receptor deficiency augmented AngII-induced atherosclerosis and plaque rupture through mechanisms involving increased oxidative stress, inflammation, and apoptosis [ 184 ]. All of these complications were abolished by overexpression of ACE2 [ 54 , 186 , 187 , 188 , 189 ] and treatment with ACE2 activator (DIZE) [ 190 , 191 ] or subcutaneous Ang(1-7) [ 192 ]. Taken together, there is evidence regarding components of ACE2-Ang(1-7)-Mas axis involvement in CAD devolvement and progression; however, to further elucidate the therapeutic potential of modulation of this axis will require utilization of more selective tools to separate the upstream RAS effects provided by ACE inhibitors or AT1 blockers in general CAD therapy.…”
Section: Ace2 Deficiency-related Pathologies Underlying Hypoxiamentioning
confidence: 99%